Accurate potential energy curves, spectroscopic parameters, transition dipole moments, and transition probabilities of 21 low–lying states of the CO+ cation. (May 2018) - Xing, Wei; Shi, Deheng; Zhang, Jicai; Sun, Jinfeng; Zhu, Zunlue
Highlights: Transition dipole moments between different Λ-S states are calculated. Radiative lifetimes of vibrational levels of several states are obtained. Transition probabilities are discussed. SOC effect on the spectroscopic parameters and vibrational levels is commented. Abstract: This paper calculates the potential energy curves of 21 Λ–S and 42 Ω states, which arise from the first two dissociation asymptotes of the CO + cation. The calculations are conducted using the complete active space self–consistent field method, which is followed by the valence internally contracted multireference configuration interaction approach with the Davidson correction. To improve the reliability and accuracy of the potential energy curves, core–valence correlation and scalar relativistic corrections, as well as the extrapolation of potential energies to the complete basis set limit are taken into account. The spectroscopic parameters and vibrational levels are determined. The spin–orbit coupling effect on the spectroscopic parameters and vibrational levels is evaluated. To better study the transition probabilities, the transition dipole moments are computed. The Franck–Condon factors and Einstein coefficients of some emissions are calculated. The radiative lifetimes are determined for a number of vibrational levels of several states. The transitions between different Λ–S states are evaluated. Spectroscopic routines for observing these states are proposed. The spectroscopic parameters, vibrational levels, transition dipole moments, and transition probabilities reported in this paper can be considered to be very reliable and can be used as guidelines for detecting these states in an appropriate spectroscopy experiment, especially for the states that were very difficult to observe or were not detected in previous experiments. Graphical abstract: This work calculates the potential energy curves and spectroscopic parameters of all the states and computes the transition dipole moments between different Λ-S states. The FC factors and Einstein coefficients of many emissions are evaluated. The radiative lifetimes are determined for the vibrational levels of several states. Spectroscopic routines for observing these states are proposed. The SOC effect on the spectroscopic parameters and vibrational levels is insignificant for all the Ω states except for the vibrational levels of 2 2 Δ3/2 and 2 2 Δ5/2 states. The spectroscopic parameters, vibrational levels, transition dipole moments, and transition probabilities reported in this paper can be considered to be very reliable and can be used as guidelines for detecting these states spectroscopically in the near future. .